2022
DOI: 10.3390/ijerph19074104
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Mechanisms for Carbon Emission Abatement Considering Consumers’ Low-Carbon Awareness under Cap-and-Trade Regulation

Abstract: In the era of sustainable development, reducing carbon emissions and achieving carbon neutrality are gradually becoming a consensus for our society. This study explores firms’ incentive mechanisms for carbon emission abatement in a two-echelon supply chain under cap-and-trade regulation, where consumers exhibit low-carbon awareness. To boost the manufacturer’s motivation for abatement, the retailer can provide four incentive strategies, i.e., price-only (PO), cost-sharing (CS), revenue-sharing (RS), and both (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Numerous individuals' characteristics have been investigated in the context of diverse online green shopping process literature (Kim et al, 2017;Jiang et al, 2020). Different individual's complex information processing for low-carbon product purchasing is always discussed in the sustainable management literature (Halder et al, 2020;Xue et al, 2022). With the proposal of South Korean "Green New Deal" and Chinese "30•60 carbon peak and neutrality strategic goals, " the environmental awareness of residents in both countries has been considerably improved (Ding et al, 2018), especially college students who received advanced education.…”
Section: Comparison Of South Korean and Chinese College Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous individuals' characteristics have been investigated in the context of diverse online green shopping process literature (Kim et al, 2017;Jiang et al, 2020). Different individual's complex information processing for low-carbon product purchasing is always discussed in the sustainable management literature (Halder et al, 2020;Xue et al, 2022). With the proposal of South Korean "Green New Deal" and Chinese "30•60 carbon peak and neutrality strategic goals, " the environmental awareness of residents in both countries has been considerably improved (Ding et al, 2018), especially college students who received advanced education.…”
Section: Comparison Of South Korean and Chinese College Studentsmentioning
confidence: 99%
“…Following that, more and more low-carbon products appear in online and offline markets, and global scholars and managers in various fields are paying attention to environmental issues (ElHaffar et al, 2020). Especially, in the field of cross-border e-commerce (CBEC), the emergency of low-carbon products and green consumption represents the inevitable trend (Xue et al, 2022). Thus, improving consumers' purchase intention for low-carbon products on the CBEC platform can effectively solve global environmental concerns and achieve the dual growth of economic and environmental performance (Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sayed et al (2020) proposed that when an agent conceals private information and the principal cannot understand the agent's behavior, an effective incentive contract can regulate the agent's behavior. Xue et al (2022) found that core enterprises can effectively promote the emission reduction of non-core enterprises through incentive contracts by building a principal-agent model between the core and other enterprises in the supply chain. It can be seen that designing incentive contracts can solve some problems in low-carbon supply chain coordination under asymmetric information.…”
Section: The Low-carbon Supply Chain Operation Under the Situation Of...mentioning
confidence: 99%
“…Consequently, Aiying and Risto [ 25 ] applied the carbon trading system to large-scale industrial activities; Chai et al [ 26 ] studied how carbon allowances and carbon emissions trading can be conducive to remanufacturing, and discovered that in the long run manufacturers should invest in low carbon production technology; Aldieri et al [ 27 ] found that the green innovation subsidy policy can help the enterprises to adopt to the green technology and increase their level of employment; Huang et al [ 28 ] found that the green credit in a supply chain is good for social welfare and environmental benefit. Lee [ 29 ] found that the supply chain members’ participation in green innovation activities could achieve a win-win scenario in the CLSC; Xia et al [ 30 ] found that the emergence of carbon trading systems will affect the low-carbon behavior of the OEMs; Yang et al [ 31 ] studied the selection of remanufacturing collection modes under the carbon emission trading system; Li et al [ 32 ] found that the government subsidy strategy could reduce carbon emissions; Lv and Li [ 33 ] studied the influence of green consumers on enterprises’ green innovation and found that enterprises would choose to carry out green innovation when green consumers exist in the market; Wang et al [ 34 ] found that stringent regulations do not imply more remanufacturing; Cheng et al [ 35 ] found that manufacturers will increase their green technology investment level under the carbon emission constraint; Sarkar et al [ 36 ] found that green innovation can increase the sale quantity of the product; Xue et al [ 37 ] found that consumers’ low-carbon awareness could increase the profits of supply chain members; Yang et al [ 38 ] did a series of studies on the introduction of carbon emissions trading into remanufacturing. From the above research, it is evident that under the carbon trading system, producers’ production behaviors are constrained in such a way that they will be actively assuming the social responsibility of reducing carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%